Creating a family through surrogacy: Negotiating parental positions, familial boundaries and kinship practices - Teschlade, Julia; Peukert, Almut (My University, 2019)
This article focuses on male same-sex couples who fulfil their wish for a child through gestational surrogacy. As two-father families they must engage with society’s expectation that every child has both a mother and a father. Thus, the position of the mother must be filled, or at least accounted for. The empirical data derive from interviews with male samesex couples from Germany. Following the grounded theory approach, we analyse the couples’ ‘doing (being) family’ from two perspectives. First, we discuss how family roles are negotiated within the family formation process. The fathers employ different strategies to address the issue of the ‘absent mother’. Second, we examine how the couples draw boundaries in family formation processes to ensure that they are seen as the child’s only parents. We argue that social discourses lack broader definitions of (family) relations beyond the gendered categorizations of father and mother.
Keywords: doing family; egg donation; Elternschaft; Familie; gay fathers; parenthood; surrogacy; Vaterschaft; ddc:300